Design of the HPTN 065 (TLC-Plus) study: A study to evaluate the feasibility of an enhanced test, link-to-care, plus treat approach for HIV prevention in the United States. (August 2017) - Gamble, Theresa; Branson, Bernard; Donnell, Deborah; Hall, H Irene; King, Georgette; Cutler, Blayne; Hader, Shannon; Burns, David; Leider, Jason; Wood, Angela Fulwood; G. Volpp, Kevin; Buchacz, Kate; et al.
Background/Aims: HIV continues to be a major public health threat in the United States, and mathematical modeling has demonstrated that the universal effective use of antiretroviral therapy among all HIV-positive individuals (i.e. the "test and treat" approach) has the potential to control HIV. However, to accomplish this, all the steps that define the HIV care continuum must be achieved at high levels, including HIV testing and diagnosis, linkage to and retention in clinical care, antiretroviral medication initiation, and adherence to achieve and maintain viral suppression. The HPTN 065 (T est, L ink-to-C areP lus Treat [TLC-Plus]) study was designed to determine the feasibility of the "test and treat" approach in the United States. Methods: HPTN 065 was conducted in two intervention communities, Bronx, NY, and Washington, DC, along with four non-intervention communities, Chicago, IL; Houston, TX; Miami, FL; and Philadelphia, PA. The study consisted of five components: (1) exploring the feasibility of expanded HIV testing via social mobilization and the universal offer of testing in hospital settings, (2) evaluating the effectiveness of financial incentives to increase linkage to care, (3) evaluating the effectiveness of financial incentives to increase viral suppression, (4) evaluating the effectiveness of a computer-delivered intervention to decrease risk behavior in HIV-positive patients in healthcare settings, and (5) administering provider and patient surveys to assess knowledge and attitudes regarding the use of antiretroviral therapy for prevention and the use of financial incentives to improve health outcomes. The study used observational cohorts, cluster and individual randomization, and made novel use of the existing national HIV surveillance data infrastructure. All components were developed with input from a community advisory board, and pragmatic methods were used to implement and assess the outcomes for each study component. Results: A total of 76 sites in Washington, DC, and the Bronx, NY, participated in the study: 37 HIV test sites, including 16 hospitals, and 39 HIV care sites. Between September 2010 and December 2014, all study components were successfully implemented at these sites and resulted in valid outcomes. Our pragmatic approach to the study design, implementation, and the assessment of study outcomes allowed the study to be conducted within established programmatic structures and processes. In addition, it was successfully layered on the ongoing standard of care and existing data infrastructure without disrupting health services. Conclusion: The HPTN 065 study demonstrated the feasibility of implementing and evaluating a multi-component "test and treat" trial that included a large number of community sites and involved pragmatic approaches to study implementation and evaluation.